Mathematica Module for Singularity Free Computations of Euler Parameters (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper,a Mathematica module for singularityfree computations of Euler parameters was established .The basic idea  that we follow in  developing  these  computationsis  to make the values of  the denominators of the fractions used to compute the parameters always maximum, so by this artifice we avoid the divisions by small quantities that causes singularities.